Quantifying the effect of environmental drivers on water conservation variation in the eastern Loess Plateau, China - Wang, Jinfeng; Wu, Taoli; Li, Qing; Wang, Sheng (Ecological indicators, 2021)
•The pattern of water conservation was significantly related to land use types.•Other human activities were key factor for water conservation reduction in P1-P2.•Human water consumption contributed 39.5% of variation in water conservation. The Loess Plateau is famous for its water shortages and soil erosion, quantitatively assessing the water conservation function is of great significance to maintain regional ecological security. Zhanghe River Basin with severe water conflicts in eastern Loess Plateau, was selected to investigate the variation characteristics of water conservation. The results showed that water conservation decreased slightly from 1960 to 2016, with a rate of 1.1 × 108 m3/10a. The mean annual water conservation (MAWC) is 31.46 × 108 m3, and accounted for 32% of the precipitation. The spatial pattern of water conservation and land use type were significantly correlated: More water resources (>213 mm) were conserved in the north hilly region with high vegetation coverage, while water resources were less (<140 mm) conserved in the south cropland and construction land. Using the calibrated Soil and Water Assessment Tool (SWAT), the contribution rates of climate change, land use, and other human activities (e.g. engineering measures, water consumption) on water conservation were quantitatively estimated through setting several different environmental scenarios. The research period (1974–2016) was divided into the baseline period (P0: 1974–1994), dramatically-increased period (P1: 1995–2005) and weakly-increased period (P2: 2006–2016). The attribution results indicated that other human activities were the dominant factor, and exerted greater effects on the increase of water conservation in the recent decades, with an increasing contribution from 82.88% in P1 to 122.16% in P2. Climate change was the secondary factor, and it increased water conservation in P1 but reduced it in P2, with the contribution from 18.01% to −15.45%. The contributions of climate change, land use/cover change (LUCC) and other human activities to water conservation reduction during P1-P2 were 32.53%, 1.67%, and 65.80%, respectively. In the recent decades, other human activities have become the most important factors on water conservation reduction, in which human water consumption contributed to 60.1%